Determinants of Social Media Usage and Their Role in Enhancing Business Performance: Evidence from Medical Tourism Service Providers - NAJAR, Manel; ZAIEM, Imed (Revue Internationale des Sciences de Gestion, 2025)
This research examines the antecedents and performance outcomes of social media use in the medical tourism sector, drawing on the Technology Acceptance Model (TAM), the Technology–Organization–Environment (TOE) framework, and the Resource-Based View (RBV). Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed to validate the proposed conceptual model. Data were collected through an online survey administered to 133 medical service providers in Tunisia. The results show that information intensity and perceived usefulness have a significant positive effect on social media usage, while perceived ease of use does not exhibit a significant influence. In addition, social media usage positively affects the marketing performance of medical tourism providers. This study highlights the importance of evaluating social media adoption from a managerial perspective. For professionals in the medical tourism industry, optimizing social media strategies can enhance marketing performance and strengthen competitive positioning.